Pre-match Warm-Up Dynamics and Workload in Elite Futsal - Silva, Nuno; Travassos, Bruno; Gonçalves, Bruno; Brito, João; Abade, Eduardo (Frontiers in Psychology, 2020)
Warming-up prior to competition is a widely accepted strategy to increase players’ readiness and achieve high performances. However, pre-match routines are commonly based on empirical knowledge and strongly influenced by models emerging from elite team practices. The aim of the present study was to identify and analyze current pre-match warm-up practices in elite futsal. Forty-three elite players were analyzed during their pre-match warm-up routines during the Portuguese Futsal Cup Final 8. Warm-up tasks were classified according to duration, type of activity, sequence and structure. External load variables included the total distance covered, total distance covered per minute, running distance per minute, sprinting distance per minute, number of accelerations per minute and number of decelerations per minute. Results highlighted that warm-up routines lasted for 27.5 ± 9.2 minutes and included 9 major different tasks. Open-skill activities were prioritized by coaches; competitive and non-competitive futsal-specific tasks were included in 90% of the total warm-up routines. The intensity progressively increased during warm-ups, mainly because of the higher number of accelerations and decelerations per minute. Futsal warm-ups frequently include specific and representative tasks in order to establish settings able to prepare players for the upcoming game. When designing pre-match warm-up routines, coaches should be aware that duration, sequence and type of tasks may affect players’ acute performance and readiness.